Single phase 21 level hybrid multilevel inverter with reduced power components employing low frequency modulation technique - Meraj, S.T. (Institute of Advanced Engineering and Science, 2020)
This paper introduces a new hybrid topology of multilevel inverter capable of generating 21-level output voltage. The proposed topology is built using the combination of cross-switched bridge and a conventional full H-bridge. Compared to the conventional topologies and other hybrid topologies, the newly introduced multilevel inverter has the ability to maximize the number of voltage levels utilizing lower number of DC voltage sources, integrated bipolar transistor (IGBT) switches and gate drivers. A low frequency modulation technique is used to generate the ideal multilevel output voltage and gate pulses. Furthermore, the proposed topology is validated by building a hardware prototype and obtaining relevant experimental results. The acquired simulated and experimental results indicate the proper functioning of the proposed hybrid topology along with the compatibility of the applied modulation technique. Â© 2020, Institute of Advanced Engineering and Science. All rights reserved.